Peripheral Blood Monocyte Synthesis of Plasminogen Activator Inhibitor 2 in Response to Native and Modified LDL - Ritchie, Helen; Jamieson, Alec; Booth, Nuala A (Thrombosis and Haemostasis, 1995)
Fibrin deposition is a characteristic feature of the atherosclerotic plaque. The balance of fibrinolytic activity is modulated by plasminogen activators (PAs) and plasminogen activator inhibitors (PAIs). We examined expression of components of the fibrinolytic system by peripheral blood monocytes following stimulation by native LDL and LDL modified by acetylation, copper oxidation or minimal modification. Monocytes responded to LDL stimulation by increased production of PAI-2, with no corresponding increase in u-PA. PAI-1 was detected but did not change relative to untreated control; u-PA was undetectable in all samples. Native LDL consistently upregulated PAI-2; this stimulation was not inhibited by inclusion of antioxidants. Acetylated, copper oxidized and minimally modified LDLs increased production of PAI-2, but the ability to stimulate PAI-2 synthesis varied between preparations of modified LDL. Increased levels of PAI-2 in a local environment such as the artery wall may promote fibrin persistence.